Analyzing Main Character Development In Turning Red Through Maslow’s Hierarchy Of Needs: A Psychological And Educational Perspective - Awwaliyah, Rahmah Nada El; Sinaga, Juwita Boneka; Adam, Adam (UNIVERSITAS PAKUAN, 2025)
This research explores the application of Maslow's Hierarchy of Needs in analyzing, which is the main character development in the Turning Red movie (2022) and the implications for character education. By analyzing the main character “Meilin Lee’s” psychological growth, this research aims to show how Maslow’s theory can be applied into educational settings, especially in understanding student motivation, identity formation, and the social interactions. By using a qualitative descriptive method, this study conducts the main character analysis through a close examination of the movie’s narrative, dialogues, and character interactions. Every data was collected through repeated observations and thematic analysis, aligning Mei’s experiences with Maslow’s five levels of needs: physiological, safety, love and belonging, esteem, and self-actualization. The research findings reveal that this movie reflects the gradual fulfillment of these needs, with significant emphasis on self-acceptance, resilience, and social belonging. Her struggles with family expectations and personal identity illustrate key psychological challenges faced by adolescents. Also, this study suggests that Turning Red can serve as an engaging educational tool for teaching psychological concepts and character development in formal and informal learning environments. The collaboration of movies in educational curricula may enhance students' understanding of their self-growth, emotional intelligence, and social adaptation.